Public integrity - Dobel, J. Patrick (Baltimore, Md. Johns Hopkins University Press, 1999)
In this groundbreaking book, J. Patrick Dobel describes and analyzes the elements that constitute integrity in public office. Drawing on case studies, memoirs, interviews, and fiction (e.g., John Le Carr)̌, Dobel addresses such issues as when to resign and when to stay in office. He examines the temptations of power, the relation between private and public life, and the role of honor and prudence in making personal decisions. He applies not only moral theory but also the insights of history, organizational theory, and psychology. Unlike most political ethics books, Public Integrity puts personal responsibility at the center of public morality, examining not just the responsibilities of office but also the role of personal moral commitments and promises. This timely book reminds us of the importance of public integrity as well as the demands and challenges that often threaten that integrity, especially in a liberal democracy such as the United States.
Includes bibliographical references (p. [223]-252) and index.
Keywords: Public administration --Moral and ethical aspects